African identities : race, nation and culture in ethnography, pan-Africanism and Black literatures - Kanneh, Kadiatu, 1966- (Routledge, 1998)
Kanneh locates Black identity in relation to Africa and discovers how histories connected with the domination, imagination, and interpretation of Africa are constructive of a range of political and theoretic parameters around race.